The Navier-Stokes problem in the 21st century - Lemarié, Pierre Gilles 1960- (CRC Press is an imprint of Taylor & Francis Group, an Informa business, 2016)
The complete resolution of the Navier-Stokes equation-one of the Clay Millennium Prize Problems-remains an important open challenge in partial differential equations (PDEs) research despite substantial studies on turbulence and three-dimensional fluids. The Navier-Stokes Problem in the 21st Century provides a self-contained guide to the role of harmonic analysis in the PDEs of fluid mechanics